Early Recognition of Pediatric Strokes in the Emergency Department: Epidemiology, Clinical Presentation, and Factors Impeding Stroke Diagnosis in Children - Si Qi Tan; Wen Qi Cher; Shu-Ling Chong; Angelina Su Yin Ang; Sashikumar Ganapathy; Derrick Wei Shih Chan; Ronald Ming Ren Tan (Korean Child Neurology Society, 2023)
Purpose Strokes are challenging to diagnose in pediatric emergency departments (EDs) as level of suspicion is low and atypical presentations are common. We analyzed clinical features, epidemiology and factors of delayed identification in arterial ischemic strokes (AIS) and hemorrhagic strokes (HS). Methods Single-center retrospective cohort study of children aged between 29 days and 18 years old diagnosed with stroke between July 2016 to June 2021. Results Among 36 children, 11 (30.5%) had AIS, 25 (69.4%) had HS. Median age for AIS was 9 years (interquartile range [IQR], 2 to 9) and HS 9 years (IQR, 1 to 11.5) (P=0.715). Focal neurological deficit was seen in 72.7% of AIS and 20% of HS (P=0.006). Only 18.2% of AIS and 52.0% of HS presented within 6 hours of symptoms. Median time from symptom onset to ED presentation was 24 hours (IQR, 12 to 28) for AIS and 7 hours (IQR, 1.8 to 48) for HS (P=0.595). Most (85.6%) arrived by own transport. Median time from presentation to neuroimaging was 7 hours (IQR, 0.9 to 7) for AIS and 4.8 (IQR, 1.3 to 16.8) hours for HS (P=0.376). Eleven patients, 9/25 (36.0%) HS and 2/11 (18.2%) AIS, did not have stroke as differential diagnosis at ED (P=0.714). Common initial diagnoses were viral illness or headaches. On univariate analysis, age <1 (odds ratio [OR], 17.5; 95% confidence interval [CI], 1.2 to 250.4; P=0.035) and absence of focal neurological deficit (OR, 13.091; 95% CI, 1.5 to 117.9; P=0.022) were significant factors for delayed identification. Conclusion Index of suspicion for pediatric strokes among caregivers and clinicians should be increased. Public awareness campaigns are recommended.